2013
DOI: 10.1118/1.4813999
|View full text |Cite
|
Sign up to set email alerts
|

SU-D-105-03: Developing QA Procedures for Gated VMAT SABR Treatments

Abstract: Purpose: To develop a QA procedure for gated VMAT SABR liver cancer treatments and investigate the gating parameters for acceptable plan delivery in terms of the dose to a moving volume and treatment delivery time. Methods: 10 patient plans for VMAT SABR liver were created using the Eclipse™ TPS. The verification plans were then transferred to a CT‐scanned Quasar™ phantom and delivered on a TrueBeam™ linac using a 10FFF beam and Varian's RPM system for respiratory gating. Two kinds of breathing patterns were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Unstable breathing patterns and asynchronous target motions to respiratory phases might significantly affect the accuracy of dose delivery in gated radiotherapy [8,9]. Several studies have suggested that respiratory-induced tumor movement should be considered in overall radiation therapy procedures such as treatment planning, image guidance, beam delivery, and QA verification [1014].…”
Section: Introductionmentioning
confidence: 99%
“…Unstable breathing patterns and asynchronous target motions to respiratory phases might significantly affect the accuracy of dose delivery in gated radiotherapy [8,9]. Several studies have suggested that respiratory-induced tumor movement should be considered in overall radiation therapy procedures such as treatment planning, image guidance, beam delivery, and QA verification [1014].…”
Section: Introductionmentioning
confidence: 99%